BIM Utilization to Eliminate Claims, Risks, and Improve Productivity in Construction Projects - Bakr, Emad Hashem; Elbeltagi, Emad; Tantawy, Mohamed (Salehan Institute of Higher Education, 2025)
Delays, cost overruns, and disputes have traditionally plagued the construction industry. These issues arise from poor management and the complexities of construction projects. Given this situation, this research sought to identify and quantitatively prioritize the factors leading to claims/disputes, risks, and the construction activity productivity. At the same time, it aimed to measure the extent to which the BIM approach mitigates such factors. A mixed methodological approach was utilized, which included a structured questionnaire survey and two case studies. For quantitative data analysis, advanced techniques and tools of IBM SPSS and AMOS were used, which included mean analysis, Standard Deviation (SD), Relative Importance Index (RII), Confirmatory Factor Analysis (CFA), Exploratory Factor Analysis (EFA), and Structural Equation Modeling (SEM). The findings confirmed the hypothesis of this research, showing BIM implementation directly and substantially improves productivity, as evidenced by the 28% reductions in disputes, 31% in communication efficiency, and 24% in overall productivity. Moreover, SEM results confirmed the existence of positive causal relationships regarding BIM adoption and cost control, schedule compliance, and safe work performance. This study conclusively demonstrates that BIM is a dynamic management approach to enhancing stakeholder coordination, minimizing disputes, and ultimately ensuring project viability.